Animal camouflage 3-D close up - Gilpin, Daniel (San Diego : Quarto Children's Books, 2009)
Look at the extraordinary ways that animals disguise themselves, including four incredible pop-up scenes. Discover the fascinating ways that animals use camouflage to hide from predators or sneak up on their prey. All kinds of creatures are the masters of disguise, from curious insects that look like a leaf or flower, to the tiger and clouded leopard stalking among the shadows of the jungle.
H
b
b